ANALISIS KECERDASAN MATEMATIS PADA RASA EMPATI SISWA SEKOLAH DASAR - Fadilatul Laila; Fahra Putri Ardita; Cucu Atikah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to analyze the relationship between mathematical intelligence and empathy in elementary school students. Mathematical intelligence, which is measured through students' ability to solve mathematical problems, has a significant impact on their social and emotional development, including empathy. Using a qualitative approach, this research involved students from several elementary schools in Indonesia, using mathematics test instruments and questionnaires to measure levels of empathy. The research results show that there is a positive relationship between mathematical intelligence and empathy, where students with higher mathematical abilities tend to have better levels of empathy. This research also discusses the implications of these findings for the education curriculum in elementary schools, as well as the importance of developing these two aspects simultaneously to create a more sensitive and intelligent generation.